Imagining Events Alternative to the Present Can Attenuate Delay Discounting - Ciaramelli, Elisa; Sellitto, Manuela; Tosarelli, Giulia; di Pellegrino, Giuseppe (Frontiers in Behavioral Neuroscience, 2019)
Previous studies have shown that delay discounting (DD), the tendency to prefer smaller-immediate to larger-delayed rewards, decreases following vivid imagination of future events. Here we test the hypothesis that imagining complex events alternative to direct (perceptual) experience, whether located in the future, the past, or even the present, would reduce DD. Participants (N = 250) imagined future events (Future condition), remembered past events (Past condition), imagined present events (Present-imagine condition), or reported on the current events (Present-attend condition), and then made a series of intertemporal choices about money and food. Compared to attending to the present, imagining the future reduced DD, but this only held for individuals who claimed vivid pre-experiencing of future events. Importantly, a similar attenuation of DD was found in the Past and Present-imagine conditions, suggesting that a shift in perspective from the perceptual present towards mentally constructed experience can downplay the appraisal of immediate rewards in favor of larger-delayed rewards, regardless of the location of the imagined experience in subjective time.